Study of some significant parameters about the dynamic of the arms to evaluate the vertical jump in volleyball athletes, category 13-15 from the sport school Ormani Arenado Llonch - Enrique Henríquez Hernández; Tania Rosa García Hernández; Miriam Camejo Expósito (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2016)
To improve the yield in the vertical jump for many scientists, trainers and athletes has been and it continues being a polemic objective in the training for the volleyball players keeping in mind the participation that has this task motorboat in question, without doubts the Cuban School of Volleyball keeping in mind the characteristics of our players it has potentialized the saltabilidad of the jugadoras there is inclination of the years for it becomes it necessary to study and to evaluate the capacity miodinámica of the musculature of the inferior members to give continuity to this problem takes like sample in our study the athletes of the category 13-15 years of the EIDE of Pinegrove of the River to which you/they were carried out a traverse study in the stage of general physical preparation where you study the restored miodinámica of the inferior members in different laboratory test Squat Jump and I jump with against movements starting from a contact doormat built in Pinegrove of the River, field test like long jump without impulse, test of Power of Lewis, test of relative force for inferior members, being significant securities of correlation. Starting from the results individual suggestions were offered for the training of this athletes.